2021
DOI: 10.1007/s00167-021-06581-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased tibial tubercle-trochlear groove and patellar height indicate a higher risk of recurrent patellar dislocation following medial reefing

Abstract: Purpose Identifying anatomical risk factors on recurrent dislocation after medial reefing is important for deciding surgical treatment. The present study aimed to retrospectively analyze the preoperative magnetic resonance imaging (MRI)-based parameters of patients treated with medial reefing and whether these parameters lead to a higher risk of recurrent dislocation. Methods Fifty-five patients (18.6 ± 6.6 years) who underwent medial reefing after primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Fifteen studies found trochlear dysplasia to be a significant risk factor for recurrent PD (OR 2.53–18.945) and (hazard ratio (HR) 2.3–3.27) [2, 6, 14, 20, 30, 33, 37, 38, 41, 42, 55, 59, 60, 67, 73]. Three studies did not find a significant association to PD [1, 26, 57] (Table 1 and Appendix 3; Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies found trochlear dysplasia to be a significant risk factor for recurrent PD (OR 2.53–18.945) and (hazard ratio (HR) 2.3–3.27) [2, 6, 14, 20, 30, 33, 37, 38, 41, 42, 55, 59, 60, 67, 73]. Three studies did not find a significant association to PD [1, 26, 57] (Table 1 and Appendix 3; Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…In clinical work, many researchers agreed that TT-TG distance less than 20 was appropriate [ 34 ]. Researchers claimed that the increase in TT-TG distance would aggravate the lateral stress of patella in patients and even lead to the recurrence of patellar dislocation [ 35 ]. Tibial tubercle transfer reduced TT-TG distance by moving the tibial tubercle inward in response to the lateralization of the tibial tubercle relative to the femoral trochlear groove [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sample size of this study was 60 cases, 30 cases in each of the 2 groups. Inclusion criteria: patients aged 18 to 45 years (2) more than 2 dislocations after the first dislocation; painful patellar instability symptoms or subluxation; positive patellar apprehension test; [14] excessive patellar tilt angle on computed tomography (CT) and MPFL tear on magnetic resonance imaging. Exclusion criteria: age < 18 years or more than 45 years; bony structural abnormalities: Insall-Salvati index ≥ 1.2, [15] tibial tuberosity-trochlear groove distance of ≥ 20 mm, [16] Severe Trochlear Dysplasia (Dejour type B, C, or D), [17] Femoral anteversion angle ≥ 25°, [18] and previous surgery on the affected knee, all performed by a surgically experienced chief surgeon.…”
Section: Methodsmentioning
confidence: 99%